Linking Human Dignity, Vulnerability and Virtue Ethics - Keenan, James F. (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
An ethics of vulnerability, that develops out of an imago Dei/human dignity presupposition, can provide a foundation for a virtue ethics that orients us toward the right responsiveness to contemporary challenges. It explores a vulnerability rooted in imago Dei language and then further develops a vulnerability foundation that is based not primarily on need but on capacity. It concludes offering particular virtues (humility, vigilance, mercy and hospitality) that help in the practice of recognizing human dignity.